2023
DOI: 10.18632/aging.204867
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1-mediated MET/AXL signaling enhances sorafenib resistance in hepatocellular carcinoma by escaping ferroptosis

Abstract: Sorafenib, a small-molecule inhibitor targeting several tyrosine kinase pathways, is the standard treatment for advanced hepatocellular carcinoma (HCC). However, not all patients with HCC respond well to sorafenib, and 30% of patients develop resistance to sorafenib after short-term treatment. Galectin-1 modulates cell-cell and cell-matrix interactions and plays a crucial role in HCC progression. However, whether Galectin-1 regulates receptor tyrosine kinases by sensitizing HCC to sorafenib remains unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The authors observed that galectin-1 knockdown and overexpression were able to reduce and increase sorafenib resistance, respectively. In turn, both sorafenib-resistant HCC cells and HCC cells overexpressing galectin-1 exhibited increased Axl phosphorylation ( 124 ). Decreased chemoresistance to cisplatin was detected in human HCC MHCC-97L cells overexpressing the miRNA 34a-5p, a microRNA that directly targets Axl ( 125 ).…”
Section: Gas6 and Tam Receptorsmentioning
confidence: 99%
“…The authors observed that galectin-1 knockdown and overexpression were able to reduce and increase sorafenib resistance, respectively. In turn, both sorafenib-resistant HCC cells and HCC cells overexpressing galectin-1 exhibited increased Axl phosphorylation ( 124 ). Decreased chemoresistance to cisplatin was detected in human HCC MHCC-97L cells overexpressing the miRNA 34a-5p, a microRNA that directly targets Axl ( 125 ).…”
Section: Gas6 and Tam Receptorsmentioning
confidence: 99%